The business of art unveiled New York art dealers speak up - Klein, Ulrike (Lang, 1994)
Interviews with New York art dealers.
Keywords: Kunsthandel; Kunst; Art galleries, Commercial -- New York (State) -- New York; Art -- Economic aspects -- New York (State) -- New York; Interview; Kunsthändler; New York, NY